The Accuracy and Cost-Effectiveness of Selective Fetal Echocardiography for the Diagnosis of Congenital Heart Disease in Patients with Pregestational Diabetes Stratified by Hemoglobin A1c - Finneran, Matthew M.; Ware, Courtney A.; Kiefer, Miranda K.; Buschur, Elizabeth O.; Foy, Pamela M.; Thung, Stephen F.; Landon, Mark B.; Gabbe, Steven G. (American Journal of Perinatology, 2019)
Objective To evaluate the accuracy of antenatal diagnosis of congenital heart disease (CHD) using screening methods including a combination of elevated hemoglobin A1c, detailed anatomy ultrasound, and fetal echocardiography.Study Design This is a retrospective cohort study of all pregnancies complicated by pregestational diabetes from January 2012 to December 2016. The sensitivity, specificity, positive predictive value, and negative predictive value were calculated for each screening regimen. The incremental cost-effectiveness ratio (ICER) was calculated for each regimen with effectiveness defined as additional CHD diagnosed.Results A total of 378 patients met inclusion criteria with an overall prevalence of CHD of 4.0% (n = 15). When compared with a detailed ultrasound, fetal echocardiography had a higher sensitivity (73.3 vs. 40.0%). However, all cases of major CHD were detected by detailed ultrasound (n = 6). Using an elevated early A1c > 7.7% and a detailed ultrasound resulted in a sensitivity and specificity of 60.0 and 99.4%, respectively. The use of selective fetal echocardiography for an A1c > 7.7% or abnormal detailed anatomy ultrasound would result in a 63.3% reduction in cost per each additional minor CHD diagnosed (ICER: $18,290.52 vs. $28,875.67).Conclusion Fetal echocardiography appears to have limited diagnostic value in women with pregestational diabetes. However, these results may not be generalizable outside of a high-volume academic setting.
Keywords: CHD; hyperglycemia; hemoglobin A1c; pregnancy; screening; fetal anomalies